Narrow Band Interference Elimination based on Compressed Sensing in UWB Energy Detector - Patil, Priyanka G.; Birajdar, Gajanan K. (Defence Science Journal, 2016)
Wireless communication applications with large signal bandwidth are developed tremendously in recent times. Due to large bandwidth the wide band communication causes huge power consumption and signal deterioration after addition of narrow band interference (NBI). The ultra wide band (UWB) energy detector, which is highly robust against NBI signal is presented. Compressed sensing is implemented to reduce the power consumption at the analog to digital converter with approximated message passing reconstruction. In addition to this, digital notch is employed to eliminate the NBI affected measurements from compressed version of the received signal before applying it to the energy detector. To analyze the efficiency of the detector, the energy detection and bit error probability of the detector in the absence of NBI and after mitigating NBI is compared. The simulation results are the evidence of effectiveness of the presented energy detector.